The Influence of Work Discipline and Work Motivation on Employee Performance at Airport Authority Office Region II Medan with Compensation as Intervening Variables - Ria Yuriani; M. Chaerul Rizky; Nizamuddin Nizamuddin (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study aims to determine the effect of work discipline and work motivation on employee performance at the Medan Region II Airport Authority Office with compensation as an intervening variable. This research used associative quantitative research. This research was conducted at the Medan Region II Airport Authority Office. The number used was 97 employees and all of them would be sampled using a saturated sample technique. The research model for this research is path analysis and data collection using questionnaires and survey calculating tools using Smart PLS 3.3.3. Based on the results of the research that has been done and the data analysis as explained in the previous chapter, the following conclusions are conveyed from the results of the research as follows: Work Discipline has a positive and significant effect on employee performance. Work Discipline has a negative and not significant effect on the Compensation value of the original sample. Compensation has no significant positive effect on employee performance. Work motivation has no significant positive effect on employee performance. Work motivation has a positive and significant effect on employee performance. Compensation has no effect on work discipline and employee performance indirectly. Compensation has no effect on Work Motivation and Employee Performance indirectly. Compensation has no effect on work discipline and employee performance indirectly. Compensation has no effect on Work Motivation and Employee Performance indirectly. Compensation has no effect on work discipline and employee performance indirectly. Compensation has no effect on Work Motivation and Employee Performance indirectly.